Analisis Kelayakan Usaha Perkebunan Kelapa Sawit Rakyat di Desa Tanoh Mayang Kecamatan Teunom Kabupaten Aceh Jaya - Aulora Ismatun Fadillah; Zakiah Zakiah; Agustina Arida (Jurnal Ilmiah Mahasiswa Pertanian, 2022)
Tanoh Mayang Village is one of the villages which has the highest oil palm area compared to other villages in Teunom District of Aceh Jaya Regency. Based on the survey of research sites, the average smallholder oil palm plantation in Tanoh Mayang Village is neglected with low production levels. By the existing issues, the author is interested in conducting research in the location. The purpose of this study is to know whether the smallholder oil palm plantation business in Tanoh Mayang Village is feasible when viewed from technical aspect, marketing aspect, and financial aspect.  The location of this research was chosen purposively by a sample of 19 farmers. The data used are primary data and secondary data. The analysis method uses business feasibility analysis, namely examining technical aspect, marketing aspect, and financial aspect. The results of the study indicate which is based on the results of this study indicate that the smallholder oil palm plantation business in Tanoh Mayang Village, Teunom District, Aceh Jaya Regency is feasible. From the technical aspect, it can be known that access to raw materials, labor and business location is profitable for farmers. Besides, from the aspect of marketing, it has been going well and it is feasible. Meanwhile, from the financial aspect, the results of the NPV analysis is Rp. 133,195,811.4, Net B/C is 2.0, IRR is 10.83%, and Payback Period in the 11th year of the 11th month 2nd day 27th. The results of the sensitivity analysis of the four analytical criterias is that the smallholder oil palm plantation business in Tanoh Mayang Village is still feasible to operate even when operating costs increase to 10% while benefit is fixed or when benefit decreases to 10% while the operating cost is fixed.